Flexible graphical black structural color with high angular tolerance featuring subwavelength nickel cylinder array pixels. (20th July 2020) - Zhou, Yun; Tang, Jie; Zhang, Heng; Luo, Minghui; Zhou, Lei; Shen, Su; Pu, Donglin; Chen, Linsen
Abstract: Black structural color has attracted particular interest due to its attractive applications in various fields. Until now, however, the reported graphical black structural color (GBSC) devices are mainly realized by means of electron beam lithography or focused ion beam technology, inevitably suffering from the obstacles of high production cost and time-consuming processing. Moreover, the limited and small area of the GBSC constitutes another issue for real applications and little attention has been devoted to flexible GBSC because of the limitations of this manufacturing approach. In this paper, we experimentally demonstrate and theoretically analyze a novel flexible GBSC architecture capitalized on a pixelated embedded nickel cylindrical array using a reliable, low-cost and self-developed continuously variable spatial frequency lithography. The fabricated graphical and large-area flexible GBSC sample (4 cm × 4 cm) exhibits a measured absorbance of ∼92% over the entire visible regime from 400 nm to 700 nm. Furthermore, the desirable absorptivity is well retained at incident angles up to 60°. It is anticipated that the facile, controllable and scalable approach developed here opens new exciting perspectives for industrial production.